Optimizing Business Performance Through Relationship Quality and Value Co-Creation - Prasetya, Prita (Jurnal Ilmiah Manajemen dan Bisnis, 2024)
The relationship between the concept of relationship marketing and performance is a major focus in the management and marketing literature. This research aims to explore and analyze how value co-creation and relationship quality contribute to improving performance in the context of the B2B industry. Using quantitative methods with partial least squares structural equation modeling (PLS-SEM), this study tests the hypotheses linking relationship quality, value creation, and performance. The data was obtained from a survey of 105 retailers (SEM PLS 4) to analyze the data collected from 105 retailers. Respondents consisted of managers and owners who have direct experience in customer relationship management. The analysis results show that relationship quality has a direct and positive influence on value co-creation and performance. In addition, value co-creation was also found to have a direct and positive influence on performance. Most importantly, this study reveals that value co-creation mediates the effect of relationship quality on performance. That relationship quality is an important foundation that is beneficial to the performance achieved through value co-creation between manufacturers and retailers. The theoretical contribution of this study is that it strengthens the understanding in the literature of how relationship quality and value co-creation are interrelated and jointly influence performance in a B2B context. Practically, the findings underscore the importance for firms to not only focus on building strong relationships but also actively engage in value co-creation activities to optimize business performance.